Euphorbia trigona latex nematicidal activity on the root-knot nematode Meloidogyne incognita (Research, Society and Development, 2021)
The aim of this study was to test nematicidal activity of the Euphorbia trigona latex on Meloidogyne incognita juveniles and to partially purify and characterize three proteases present in this latex. Three distinct proteases were partially purificated from E. trigona latex. They were named here trigonin 1, 2 and 3. Their molecular weights were estimated at: 36, 31 and 29 kDa, for trigonin 1, 2 and 3, respectively. The pH and temperature that provided highest protease activity were pH values of 4.0, 6.0 and 9.0, and 70 °C. The crude extract containing the three proteases present in E. trigona latex reduced significantly (p < 0.01) the number of live M. incognita juveniles in 96% after 24 hours treatment. The present study is the first report of E. trigona latex with nematicidal activity, therefore more studies regarding latex proteases action on nematodes are needed.